Odpowiedzi

2010-04-07T20:40:11+02:00
4/2x + 4 = 8
2x=4__/:2
x=2

Zad 2
x + 6 = 2
x=-4

2x - 3 =7
2x=10____/:2
x=5

3x + 1 = 2x - 4
x=-5

1/2 x + 3 = x +1
-0,5x=-2___/:(-0,5)
x=8

gr 2
Zad 1
2/3 x + 2 = 6____/*3
2x+6=18
2x=12_______/:2
x=6

Zad 2
x + 8 = 12
x=4

2x - 4 = 6
2x=10___/:2
x=5

4x + 2 = 3x - 4
x=-6
Najlepsza Odpowiedź!
2010-04-07T20:49:40+02:00
Zad 1
4/2x + 4 = 8
2x+4=8
2x=4
x=2
spr.: 4/2*2+4=8
4+4=8
8=8

Zad 2
x + 6 = 2
x=-4
spr.: -4+6=2
2=2
2x - 3 =7
2x=10
x=5
spr.: 2*5-3=7
10-3=10
10=10

3x + 1 = 2x - 4
x=-5
spr.:3(-5)+1=2(-5)-4
-15+1=-10-4
-14=-14

1/2 x + 3 = x +1/*2
x+6=2x+2/-x
6=x+2/-2
x=4
spr.: 1/2*4+3=4+1
2+3=5
5=5

Zad 1
2/3 x + 2 = 6/*3
2x+6=18/-6
2x=12
x=6
spr.:2/3*6+2=6
4+2=6
6=6

x + 8 = 12/-8
x=4
spr.: 4+8=12
12=12

2x - 4 =6
2x=10/:2
x=5
spr.: 2*5-4=6
10-4=6
6=6

4x + 2 = 3x - 4/-3x
x+2=-4/-2
x=-6
spr.: 4(-6)+2=3(-6)-4
-24+2=-18-44
-22=-22
2010-04-07T20:50:52+02:00
Zad 1
4/2x + 4 = 8
4=16x+32
-16x=32-4
-16x=28
x=-1,75

spr:
4/2*(-1,75)+4=8
4/(-3,5)+4=8
4/0,5=8
8=8

Zad 2
x + 6 = 2
x=2-6
x=-4

spr:
(-4)+6=2
2=2


2x - 3 =7
2x=7+3
2x=10
x=5

spr:
2*5-3=7
10-3=7
7=7


3x + 1 = 2x - 4
3x-2x=-4-1
x=-5

spr:
3*(-5)+1=2*(-5)-4
-15+1=-10-4
-14=-14


1/2 x + 3 = x +1
½x-x=1-3
-½x=-2
x=4

spr:
½*4+3=4+1
2+3=5
5=5



Zad 1
2/3 x + 2 = 6
2=18x+12
-18x=12-2
-18x=10
x=-⁵/₉

spr:
2/3*(-⁵/₉)+2=6
2/(-¹⁵/₉)+2=6
2/⅓=6
6=6



Zad 2
x + 8 = 12
x=12-8
x=4

spr:
4+8=12
12=12


2x - 4 = 6
2x=6+4
2x=10
x=5

spr:
2*5-4=6
10-4=6
6=6


4x + 2 = 3x - 4
4x-3x=-4-2
x=-6

spr:
4*(-6)+2=3*(-6)-4
-24+2=-18-4
-22=-22